The Potential Role of PV Solar Power System to Improve the Integration of Electric Energy Storage System - Rajesh Kumar Patnaik; P. Shyamala Bharathi; Sivaramkrishnan Mathiyalagan; Rajesh Thumma; G. Saravanan; Mohana Alanazi; V. Sivaraman; Ashraf Elfasakhany; Assefa Belay (International Journal of Photoenergy)
Integration technique is becoming effective due to the world’s largest power requirement, which has imposed a considerable need for various techniques by which electricity can be generated or integrated, as well as the assumption that integrating solar energy into nonrenewable source materials is essential to minimize the relative to nonresource consumption and thus reduces fossil fuel consumption. Photovoltaic (PV) systems are at the forefront of this transformation, harnessing the sun’s renewable electricity and converting this from DC to AC. Controlling the power grid utilizes power system photovoltaic energy production and the many ramifications of grid-scale PV energy module integration into energy systems. To completely integrate photovoltaic (PV) processes into a network, cost-effective and efficient technologies of energy storage must be used in conjunction with smart energy management systems. Electrical energy storage system (EESS) could have been used to improve a system’s stability and the performance, to recent technology improvements and quick efficiency improvements. This research provides an understanding of EESS for the photovoltaic system as well as a complete evaluation of the developing penetration level of PV. As the worldwide photovoltaic solar market is expanding, growing onsite use of PV-generated energy would become increasingly critical to ensure the stability of the grid. This research study was the first one to provide such a comprehensive overview of all forms of energy storage devices which can be used in conjunction with PV, including both thermal and electrical energy storage systems. Finally, a simulation of optimization planning is executed. The result reveals that lowering peak loads and lowering electricity usage lowers the price of electricity.